2023
DOI: 10.3390/cancers15061719
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Biopsy in Breast Cancer Patients Undergoing Neo-Adjuvant Chemotherapy: Clinical Experience with Node-Negative and Node-Positive Disease Prior to Systemic Therapy

Abstract: Background: Sentinel lymph node biopsy (SLNB) has emerged as the standard procedure to replace axillary lymph node dissection (ALND) in breast cancer (BC) patients undergoing neo-adjuvant chemotherapy (NAC). SLNB is accepted in clinically node-negative (cN0) patients; however, its role in clinically node-positive (cN+) patients is debatable. Methods: We performed a retrospective analysis of BC patients undergoing NAC and SLNB. Our aim was to evaluate the clinical significance of SLNB in the setting of NAC. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…In this setting, SLNB proved to be an acceptable procedure because of a good prognosis and low axillary failure rates in both groups of patients. No significant differences in oncological outcomes were found in the case of both axillary involvement or non-involvement after NACT, neither in the SLNB alone nor in the SLNB + ALND group [5].…”
Section: Effect Of Slnb Procedures On Local Recurrencementioning
confidence: 66%
See 2 more Smart Citations
“…In this setting, SLNB proved to be an acceptable procedure because of a good prognosis and low axillary failure rates in both groups of patients. No significant differences in oncological outcomes were found in the case of both axillary involvement or non-involvement after NACT, neither in the SLNB alone nor in the SLNB + ALND group [5].…”
Section: Effect Of Slnb Procedures On Local Recurrencementioning
confidence: 66%
“…Sentinel lymph node (i.e., the first lymph nodes in which cancer cells appear, which are most likely to spread from the primary neoplasm) biopsy (SLNB) is a minimally invasive procedure that has largely replaced axillary lymph node dissection (ALND) in early breast cancer (BC) surgery, especially in the case of no axillary lymph node involvement (cN0) and in patients at stage T1-2 cN0 early BC with one to two positive sentinel lymph nodes (SLNs). The advantages of this technique are its minimally invasive approach to the axilla and the possibility of avoiding the complications of ALND [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the treatment response in patients who received NAC, several studies indicated that positive lymph node axilla can be converted to pathologically negative status with the use of NAC in about 32–74% of patients [ 9 , 19 , 30 , 42 , 51 , 57 ]. Newman et al [ 31 ] described a ycN0 conversion rate of 32%, while Dominici et al [ 58 ] reported a pathologic complete response rate of 74%, observed in the 109 women included in their study.…”
Section: Discussionmentioning
confidence: 99%
“…The response to NAT also holds prognostic significance, being closely linked to long-term oncological outcomes [ 4 , 6 , 7 , 8 , 9 ]. Furthermore, successful tumor reduction through NAT can minimize the extent of surgery required, eliminating the need for unnecessary axillary lymph node dissection (ALND) [ 10 , 11 ] and making breast-conserving surgery (BCS) possible for patients initially considered for mastectomy [ 12 , 13 , 14 , 15 ]. In the upfront surgical setting, BCS has been proven to be a safe alternative to mastectomy in terms of overall survival (OS) [ 16 , 17 ], with recent studies even suggesting superior survival rates associated with BCS [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%